Environmental and Geomorphological Effects on the Distribution of Deep-Sea Canyon and Seamount Communities in the Northwest Atlantic - Kristen Mello-Rafter; Derek Sowers; Mashkoor Malik; Les Watling; Larry A. Mayer; Jennifer A. Dijkstra (Frontiers in Marine Science, 2021)
Deep sea canyons and seamounts are topographically complex features that are considered to be biological hotspots. Anthropogenic pressures related to climate change and human activities are placing the species that inhabit these features at risk. Though studies have examined species composition on seamounts and canyons, few have compared communities between them, and even fewer studies have examined how species’ abundances correlate with environmental conditions or geomorphology. Consequently, this study compares species composition, community structure, and environmental variables between Northwest Atlantic continental margin canyons and seamounts along the New England Seamount Chain. Geoforms were also related to the occurrence of phyla and biodiversity. Overall, there was a significant difference in species composition between canyons and seamounts with sponges, corals, sea urchins and seastars contributing heavily to observed differences. Environmental conditions of temperature and salinity and the seafloor property slope contributed significantly to communities observed on seamounts, while substrate, depth and salinity contributed significantly to canyon communities. Abundances were significantly higher in canyons, but taxonomic richness, evenness, and diversity were all greater on seamounts. In an era where climate change and human activity have the potential to alter environmental parameters in the deep sea, it is important to examine factors that influence the spatial distribution of deep-sea benthic communities.